While Galileo preys - Corin, Joshua (Don Mills, Ont. : MIRA, 2010)
As a sniper named Galileo, who has murdered fourteen innocent people, terrorizes Atlanta, former FBI field operative Esme Stuart, who has powerful inductive skills, is called back into the game to stop this twisted killer.
Keywords: Serial murderers -- Fiction; Suspense fiction